Experience with tofacitinib in Canada: patient characteristics and treatment patterns in rheumatoid arthritis over 3 years. (13th August 2019) - Pope, Janet; Bessette, Louis; Jones, Niall; Fallon, Lara; Woolcott, John; Gruben, David; Crooks, Michael; Gold, David; Haraoui, Boulos
Abstract: Objectives: To describe characteristics, treatment patterns and persistence in patients with RA treated with tofacitinib, an oral Janus kinase inhibitor, in Canadian clinical practice between 1 June 2014 and 31 May 2017. Methods: Data were obtained from the tofacitinib eXel support programme. Baseline demographics and medication history were collected via patient report/special authorization forms; reasons for discontinuation were captured by patient report. Treatment persistence was estimated using Kaplan–Meier methods, with data censored at last follow-up. Cox regression was applied to analyse baseline characteristics associated with treatment discontinuation. Results: The number of patients with RA enrolled from 2014 to 2017 was 4276; tofacitinib utilization increased during that period, as did the proportion of biologic (b) DMARD-naïve patients prescribed tofacitinib. Of patients who initiated tofacitinib, 1226/3678 (33.3%) discontinued, mostly from lack of efficacy (35.7%) and adverse events (26.9%). Persistence was 62.7% and 49.6% after 1 and 2 years of treatment, respectively. Prior bDMARD experience predicted increased tofacitinib discontinuation ( vs bDMARD-naïve, P < 0.001). Increased retention was associated with older age (56–65 years and >65 years vs ⩽45 years; P < 0.05), and time since diagnosis of 15 to <20 years ( vs <5 years; P < 0.01). In bDMARD-naïve, post-1 bDMARD, post-2 bDMARD and post-⩾3 bDMARD patients, median survival was >730, 613, 667 and 592 days, respectively. Conclusion: Since 2014, tofacitinib use in Canadian patients with RA increased, especially among bDMARD-naïve/post-1 bDMARD patients. Median drug survival was ∼2 years. Likelihood of persistence increased for bDMARD-naïve ( vs bDMARD-experienced) patients and those aged ⩾56 ( vs ⩽45) years.